Freedom, humanities and philosophy. Facing the new attacks against them that may come our way - García-Baró, Miguel (Razón y fe, 2018)
The new education plans seem to relegate philosophy and ethics. In addition to the mistake it entails and the risk that it presents to a nation that strives to be free, with the decline of philosophy in the study plans, our young people will stop learning to read, write, express themselves and reflect for the sake of an education that is supposedly technical and increasingly distant from humanities’ studies.